MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI BERMAIN KARTU ANGKA BERGAMBAR PADA ANAK USIA 4-5 TAHUN DI TK AMANAH BUNDA TANJUNG MEDAN KABUPATEN ROKAN HILIR - Deni Yarti; Zulkifli N '; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. Based on the observation, the children are lack of the ability to recognize the concept of numbers, children are not able to demonstrate the concept or symbol of numbers 1-10, the children are still incorrectly in using the symbol concept of numbers 1-10 are shown randomly, the children are still incorrectly in using the symbol of numbers that similar such as number 2 is called number 5, number 6 is called number 9. If states without the concept or symbol of number in children aged 4-5 years through playing cards illustrated in figures did in December with 15 children consist of 8 girls and 7 boys. The method used is classroom action research (PTK). The implementation of this research involves peers as an observer or observation. The stages of the research are: planning, implementation, observation, and reflection. The result of the research showed that playing number cards can improve the ability to know the concept of the symbol of number for children aged 4-5 years in Kindergarten Amanah Bunda Kecamatan Tanjung Medan Kabupaten Rokan Hilir. Increasing numbers of children recognize the concept of symbol about 22.60% in the first cycle, the second cycle about 62.04% and 98.67% for the third cycle. Keywords: symbol of numbers, numbers card picture. Keyword: To know the concept of numbers by using number card